The Deer Hunter - Cimino, Michael; Walken, Christopher; Chuck Aspegren; George Dzundza; John Cazale; John Savage; Meryl Streep; Robert De Niro (USA Universal Studios, 1978)
Michael, Steven and Nick are young factory workers from Pennsylvania who get drafted to fight in Vietnam. Before they go, Steven marries the pregnant Angela and their wedding-party is also the men's farewell party. After some time and many horrors the three friends fall in the hands of the Vietcong and are brought to a prison camp in which they are forced to play Russian roulette against each other. Michael makes it possible for them to escape, but they soon get separated again.
An in-depth examination of the way that the Vietnam war affects the lives of people in a small industrial town in the USA.
Michael Cimino
Language(s): English Subtitle(s): English, French, Spanish
1978 Oscar Academy Award Best Picture
Keywords: Drama -- Oscar Academy Award -- War